PERUMUSAN STRATEGI PEMASARAN ONLINE MENGGUNAKAN PENDEKATAN SWOT-AHP UNTUK MEMPEROLEH ALTERNATIF STRATEGI PRIORITAS - Yuwafi, Khamdan; Hussein, Ananda Sabil (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Alwaysgrow.plant is a decorative plant trading business that uses Instagram for its marketing. However, the performance of its Instagram account, i.e. @indonesiaroidplant_ has not been significant and has not provided the expected sales rate. The objective of this research is to design marketing strategies and determine a prioritized online marketing strategy for the said business. This descriptive quantitative or mixed-method research uses the combination of SWOT and AHP methods. The qualitative method, i.e. the SWOT, was used to analyze the internal and external environments of the business, while the quantitative method, i.e. the AHP, was used to determine the weight of each factor and the prioritized marketing strategy. The data was harvested from observations, interviews, and questionnaires involving six key informants considered knowledgeable and capable of handling the company’s marketing. The results indicate that the company is located at the third quadrant (-0985;0.589), which means that the most appropriate strategy is the turnaround, while WO (weakness-opportunity) serves as the alternative. At the alternative level, it was found that building engagement and online customer relationship are the prioritized alternate strategies (0.322).